Analisis Keterampilan Abad 21 Menggunakan Instrumen Tes Literasi Sains Pada Materi Asam Basa - Tri Nofiarti (Bedelau: Journal of Education and Learning, 2021)
The purpose of study was to analyzing 21th century skills (creative, critic, analyze, inovatif and sintesis) students of acid-base topic by literacy science test instrumental. Twenty five students in eleven grade participated in study. The test instrument used was the development of the literacy test instrument A. Wahyuni and E. Yusmaita (2020). Data were collected based on student answers on instrument test. The written responses were analysed to identifying 21th century skils (creative, critic, analyze, inovatif and sintesis). Results indicated that students are able to understand science, communicate science as well apply science skills to problem solving.